Agronomic performance, yield stability and selection of doubled haploid rice lines in advanced yield trials - Wira Hadianto; Bambang Sapta Purwoko; Iswari Saraswati Dewi; Willy Bayuardi Suwarno; Purnama Hidayat; Iskandar Lubis (AIMS Agriculture and Food, 2023)
Anther culture is a widely utilized technique in rice breeding because of its simplicity and effectiveness in rapidly obtaining pure lines in the form of doubled haploid plants. The selection of doubled haploid (DH) rice lines derived from anther culture in advanced yield trials is an important step for obtaining superior DH lines. We aimed to determine agronomic performance, including yield and yield stability in order to select lowland DH rice lines that are high yield and have good agronomic performance based on the selection index method. The research was conducted in Indonesia at three locations, i.e., Bogor (West Java), Indramayu (West Java) and Malang (East Java) from July to December 2022. The genotypes tested were 29 DH lines and three check varieties (Inpari-42 Agritan GSR, Inpari-18 Agritan and Bioni63 Ciherang Agritan) using a randomized complete block design (RCBD) with genotypes as a single factor and three replications. High heritability values are found in all agronomic characters, except the percentage of filled grain/panicle, the percentage of empty grain/panicle and productivity. The yield stability based on the Kang method showed that 15 lines were stable and had high productivity. Phenotypic correlation analysis showed that the number of productive tillers, days to flowering, days to harvesting, number of filled grains/panicle and percentage of filled grains all had positive values and significantly correlated with productivity. Phenotypic path analysis showed that the character of days to harvesting, number of filled grains/panicle, number of productive tillers and percentage of filled grains/panicle directly affected the productivity. Based on the weighted selection index, 12 DH lines were selected due to having a positive and higher index (8.54 to 0.28) than the Bioni63 Agritan and Inpari 18 check varieties. Among those lines, 9 DH lines were also stable based on the Kang Method.